Mentoring Narratives ON-LINE:Teaching the Principalship - Allison I. Griffith; Svitlana Taraban (Arizona State University, 2002)
The need to develop new models for preparation of school administrators has been a prominent concern in educational discourse in the last decade. Having been criticized for the inadequate preparation of the school leadership cadre, academic departments responsible for training future school administrators have had to revisit their approaches and to reframe their teaching philosophies to ensure the readiness of their graduates for the challenges and complexities of school leadership. This article reports on the new model of principals' training that has been used in York University's Principals' Qualification Program (PQP) from the late 1990s onward. One component of the program brings traditional case methodology into a computer-mediated/on-line environment. The on-line cases are narratives from the everyday lives of the Ontario school administrators who serve as mentors in the on-line environment. Situating our discussion within the context of the rapidly changing educational landscape of Ontario, we focus on the PQP model to explore experientially generated case narratives as one method for teaching and learning the work of the local school administrator. We focus particularly on the teaching and learning embedded in computer-mediated or on-line case narratives used in training teachers for school leadership. We argue that the complexities of school leadership-the social, cultural, relational, ethical and moral context of school leadership-can be taught effectively through the reflective processes of on-line case narratives. We seek to contribute to the ongoing dialogue on the potential of new pedagogies and new technologies to help prepare the competent and responsible leaders for tomorrow's schools.